Penerapan Sistem Pendukung Keputusan dalam Memilih Supplier Menggunakan Metode Analytical Hierarchy Process (AHP) - Mahdiania, Diania; Hasibuan, Muhammad Siddik (Program Studi Teknik Informatika Universitas Pamulang, 2024)
PT. LSP (Langkat Sawit Hijau Pratama) is a palm oil factory, where palm fruit or palm kernels are processed into palm oil (unfinished crude oil) which can be further processed into cooking oil, industrial oil or fuel. To get the best crude oil, superior and quality palm oil is needed, so a Decision Support System is needed in choosing suppliers to maintain good quality palm oil. A decision support system (DSS) in selecting suppliers is important because the right supplier can have a positive impact on company performance. Using a Decision Support System (DSS) with the Analytical Hierarchy Process (AHP) method in selecting suppliers can increase efficiency and effectiveness in decision making, as well as help companies choose the right suppliers and have the potential to have a positive impact on company performance. This research aims to determine the performance of the Analytical Hierarchy Process (AHP) in the Supplier selection Decision Support System and utilize the Decision Support System using the Analytical Hierarchy Process (AHP) method in making decisions as part of the consideration in choosing the right supplier. The results of this research show that by comparing decisions with the Saaty theory, priority weightings for each criterion and sub-criteria are obtained consistently or CR < 0.1. Price Criteria (0.0699), Capacity Criteria (0.2289), Quality Criteria (0.5081), Arrival Criteria (0.1932). Having obtained the final score, the best supplier has been determined using the Analytical Hierarchy Processes method, namely the BEST supplier with a total of 0.5870, and the last position is the TANI9 supplier with a total of 0.0958.